Technology Acceptance Model (TAM) Factors and Social Factors Analysis through Attitude towards to Use on Intention to Purchase of Kisah Kita Ngopi Online Café - Bramantyo, Paskalis Dio; Utami, Christina Whidya (International Business Management - Universitas Ciputra, 2022)
The covid-19 pandemic has forced entrepreneurs to switch to online sales, including Kisah Kita Ngopi (KKN) Café. It is essential to know the factors that affect a customer’s Intention to Purchase when online, such as the TAM Factors (perceived usefulness, perceived ease of use) and social factors (social influence, peer influence) attitude towards to use in using online applications. This research uses the SEM data analysis method as- sisted by Partial Least Square (PLS) software. Data collection is carried out by distributing questionnaires in the form of Google forms to people in Sidoarjo and Surabaya who have made online purchases at the KKN Café. In this study, the random sampling technique obtained 85 respondents. The results of this study indicate that (1) perceived usefulness affects atti- tude toward mobile app use, (2) perceived ease of use affects attitude to- ward mobile app use, (3) social influence does not affect attitude toward mobile app use, (4) peer influence affects attitude towards mobile app use, (5) attitude towards mobile app user does not affect intention to purchase, (6) perceived usefulness does not affect intention to purchase, (7) perceived ease of use does not affect intention to purchase, (8) social influence does not affect intention to purchase, and (9) peer influence does not affect intention to purchase. Therefore, based on the results of this study, it can be concluded that the TAM factors scores are higher than those related to social factors with regards to attitude towards to use.